Shaping a Digital Future: Examining Technology, Organization and Environment (TOE) Framework - Komathi, Wasudawan; Sim, Chia Hua (Journal of Technology Management and Business, 2024)
The uptake of e-commerce (EC) has seen a rise, increasing from 27.8% in 2019 to 37.9% in 2021, leading to a greater emphasis on online sales. However, according to SME Corporation Malaysia’s 2021 report, 65.5% of SMEs believe EC is unnecessary and prefer physical stores, while 16.6% cited a lack of skilled employees to initiate, maintain, and manage online systems. Therefore, this study examines the critical constructs surrounding the adoption of EC by SMEs in the service and other sectors in Malaysia. Utilizing the constructs of perceived benefits (H1), EC complexity (H2), top management attitude (H3), competitors’ pressure (H4), and government support (H5), the adoption of EC by Malaysian SMEs was measured and analysed. This study is supported by the Technology, Organisation, and Environment (TOE) framework dimension. The data were collected through an online questionnaire-based survey, and 155 responses were used for this study. Two of the most recognised statistical software are utilised to analyze the collected data. First, the R software was used to perform descriptive statistics. The majority of the respondents (56.77%) stated that their enterprise’s sales turnover was below RM300,000, with an additional 26.45% of respondents’ firms falling within the sales turnover range of RM300,001 to RM3,000,000. Second, the SmartPLS was utilized to test measurement and structural models. The findings indicated that the perceived benefits and EC complexity are positively associated with EC adoption by SMEs. In contrast, the results concerning top management attitude, competitor pressure, and government support indicated otherwise. As SMEs navigate the path to digitalisation, this study may be helpful to investors, owners, researchers, policymakers, and any individuals interested in knowing more about the progress of EC adoption among Malaysian SMEs.